Agar–Agar Gels Carrying Curative and Preventive Agents Against Helminths: An In Vitro Compatibility Evaluation - Izaro Zubiría; Inês Abreu; David Boso; Gustavo Pérez; Cristiana Cazapal; Rita Sánchez-Andrade; María Sol Arias; Adolfo Paz-Silva; José Ángel Hernández; Mercedes Camiña (Gels)
The global market size of animal parasiticides was valued at USD 12.9 billion in 2024. Animal deworming only results in temporary cures with little to no preventive effects; therefore, a strategy that combines animal deworming with prevention is essential in improving the control of helminths. The effectiveness of co-administrating curative and preventive agents and their compatibility were considered based on the parasitophagous fungus Mucor circinelloides, which was developed in edible agar–agar (red seaweed)-carrying dewormers. Accordingly, Petri dishes were prepared with either a biopolymer alone (control, G-C) or with the anthelmintic piperazine (550, 1102, 2210, and 5500 mg/plate) or levamisole (37.5, 75, 150, and 300 mg/plate) and were used to culture the fungus Mucor circinelloides. Strong fungal growth and high numbers of spores were observed in the presence of the anthelmintics. No differences were measured between the control plates and those containing parasiticide drugs. Similar mycelial growth patterns and sporogenesis rates were recorded for different amounts of each anthelmintic. In conclusion, this novel formulation based on biopolymers containing anthelmintics and enriched with the parasitophagous fungus represents a highly promising tool to consider for jointly deworming animals and minimizing the risks of helminth infection. Further studies are in progress to confirm these in vitro results.